Analisis Pendapatan Industri Rumah Tangga Gula Merah Tebu di Kecamatan Wih Pesam Kabupaten Bener Meriah - Teuku Fadhla; Wisma Sanjuki; Sri Fitri; Syarifuddin Syarifuddin (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
The brown sugar cane factory that is run by the people of Wih Pesam District, Bener Meriah Regency is still traditional, using technology that is still low. The labor used is still sourced from within the family and the number is not too much, namely between 5 or 6 people. The purpose of this study was to find out how much income the home industry of brown sugar cane in Wih Pesam District, Bener Meriah Regency was. The research method used is the survey method. The sampling technique used was observation (census method) with a sample size of 20 home industry entrepreneurs of brown sugar cane. The data analysis model used is profit analysis. The results showed that the average income of home industry entrepreneurs of brown sugar cane in Wih Pesam District, Bener Meriah Regency, was Rp. 5,348,058.38/month. And the home industry of brown sugar cane in Wih Pesam District, Bener Meriah Regency is profitable. This can be seen from the acquisition value of the B/C ratio of 1.09, which is greater than 1